Vascular hyperacetylation is associated with vascular smooth muscle dysfunction in a rat model of non-obese type 2 diabetes - Maria Alicia Carrillo-Sepulveda; Nicole Maddie; Christina Mary Johnson; Cameron Burke; Osina Lutz; Bamwa Yakoub; Benjamin Kramer; Dhandevi Persand (BMC, 2022)
Abstract Background Advanced type 2 diabetes mellitus (T2DM) accelerates vascular smooth muscle cell (VSMC) dysfunction which contributes to the development of vasculopathy, associated with the highest degree of morbidity of T2DM. Lysine acetylation, a post-translational modification (PTM), has been associated with metabolic diseases and its complications. Whether levels of global lysine acetylation are altered in vasculature from advanced T2DM remains undetermined. We hypothesized that VSMC undergoes dysregulation in advanced T2DM which is associated with vascular hyperacetylation. Methods Aged male Goto Kakizaki (GK) rats, a non-obese murine model of T2DM, and age-matched male Wistar rats (control group) were used in this study. Thoracic aortas were isolated and examined for measurement of global levels of lysine acetylation, and vascular reactivity studies were conducted using a wire myograph. Direct arterial blood pressure was assessed by carotid catheterization. Cultured human VSMCs were used to investigate whether lysine acetylation participates in high glucose-induced reactive oxygen species (ROS), a crucial factor triggering diabetic vascular dysfunction. Results The GK rats exhibited marked glucose intolerance as well as insulin resistance. Cardiovascular complications in GK rats were confirmed by elevated arterial blood pressure and reduced VSMC-dependent vasorelaxation. These complications were correlated with high levels of vascular global lysine acetylation. Human VSMC cultures incubated under high glucose conditions displayed elevated ROS levels and increased global lysine acetylation. Inhibition of hyperacetylation by garcinol, a lysine acetyltransferase and p300/CBP association factor (PCAF) inhibitor, reduced high glucose-induced ROS production in VSMC. Conclusion This study provides evidence that vascular hyperacetylation is associated with VSMC dysfunction in advanced T2DM. Understanding lysine acetylation regulation in blood vessels from diabetics may provide insight into the mechanisms of diabetic vascular dysfunction, and opportunities for novel therapeutic approaches to treat diabetic vascular complications.